19p13.3-GADD45B common variants and 19q13.3-PPP1R13L and 19q13.3-CD3EAP in lung cancer risk among Chinese. (1st November 2017) - Hou, Wei; Yin, Jiaoyang; Vogel, Ulla; Sun, Zhenxiang; Liang, Duohong
Abstract: Lung cancer is the most common cause of cancer-related mortality worldwide. The GADD45 gene family plays important roles in a variety of the responses to cell injury including cell cycle checkpoints, apoptosis, DNA repair and anti-tumor immunity. The 19p13.3- GADD45B encoded protein product is involved in apoptosis and inhibiting tumor growth. To evaluate the association of 19p13.3- GADD45B common variants and lung cancer risk, the present study containing 544 Chinese lung cancer cases and 550 cancer-free controls was conducted. Three htSNPs (haplotype-tagging single nucleotide polymorphism) (rs7354, rs14384, and rs3783501) covering 95% of the common haplotype diversity in 19p13.3- GADD45B and interaction of 19p13.3- GADD45B and 19q13.3- PPP1R13L and 19q13.3- CD3EAP variants and smoking-duration were explored. Genotype and allele frequencies and haplotype distributions of the 19p13.3- GADD45B 3 htSNPs were not associated with lung cancer risk after adjustment for smoking status. 19p13.3- GADD45B rs7354 was associated with lung cancer risk among ≤20 (years) smokers [C/A-A/A versus CC, OR (95% CI) = 3.20 (1.11–9.20), P  = 0.025] in a dominant model stratified by smoking duration. MDR (multifactor dimensionality reduction) analyses showed that smoking history as main effect and three-way models (smoking duration, 19p13.3- GADD45B rs3783501, 19q13.3- CD3EAP rs967591) ( P  = 0.001–0.002) indicated statistically significant association with lung cancer risk. The study identified evidence implicating DNA damage response genes on chromosome 19 in etiology of smoke-exposed lung cancer. In conclusion, our findings demonstrate that 19p13.3- GADD45B rs7354 variant and interaction between 19p13.3- GADD45B rs3783501 and 19q13.3- CD3EAP rs967591 may play a role in association with smoke-exposed lung cancer among Chinese. 19p13.3- GADD45B variants should be further evaluated in large prospective studies with molecular pathological annotations of lung cancer. Highlights: GADD45B rs7354 variant may associate with smoke-exposed lung cancer. Interaction of GADD45B and CD3EAP may involve in smoke-exposed lung cancer. Evidence implicating DNA damage response genes in lung cancer risk was identified.